Serum concentrations of 25-OH vitamin D and the pro-inflammatory interleukins IL-17, IL-23, and IL-18 in patients with plaque psoriasis - Ganeva, Maria; Tsokeva, Zhivka; Gancheva, Tanya; Hristakieva, Evgeniya; Tsoneva, Vanya; Manolova, Irena (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
AIMS: The present study aimed to assess vitamin D status and serum concentrations of pro-inflammatory cytokines IL-17, Il-23, and IL-18 in patients with chronic plaque psoriasis and their association with various demographic and clinical characteristics. METHODS: The study was conducted during the autumn/winter period on 48 patients with chronic plaque psoriasis and 48 controls. Total serum 25(OH)D level was determined with Roche Elecsys® 2010 Vitamin D total assay. Commercial ELISA kits were used for quantifying the serum levels of IL-17A, IL-18, and IL-23. RESULTS: Serum 25(OH)D had a median value of 16.95 ng/mL (IQR 10.8-23.50) for patients with psoriasis and 18.80 ng/mL (IQR 15.45-25.85) for the control group (P=0.09). A moderate negative correlation was found between PASI score and 25(OH)D levels (rs=-0.34; P=0.02). The serum levels of IL-17 (P=0.001), IL-23 (P=0.01) and IL-18 (P=0.02) were significantly higher in the patient group compared to controls. IL-17 concentrations were higher in patients with moderate to severe psoriasis compared to patients with mild psoriasis (P=0.003). No significant correlations were detected between the serum concentrations of 25(ОH)D and IL-17, IL-23, and IL-18. CONCLUSION: It was confirmed that IL-17 serum level is associated with psoriasis severity. Measurement of 25(OH)D serum concentration can be useful in patients with moderate to severe psoriasis with or without comorbidities. A direct association between 25(OH)D serum concentration and the serum concentrations of IL-17, IL-23, or IL-18 was not identified in this study.
Keywords: interleukin-18; dospělí; Interleukin-23; Female; IL-23; psoriáza; Interleukin-17; Adult; ženské pohlaví; psoriasis; interleukin-17; lidé; vitamin D; studie případů a kontrol; Vitamin D; 25-OH vitamin D; interleukin-23; Male; Case-Control Studies; IL-17; lidé středního věku; mužské pohlaví; Interleukin-18; Psoriasis; Middle Aged; IL-18; Humans